Nurturing academic leaders of tomorrow through global academic leadership excellence programme - Abd Rahman, Shukran (Human Assistance & Development International Inc. (HADI Inc.), 2025)
In today's rapidly evolving higher education landscape, academic leadership demands more than administrative oversight. It requires a comprehensive understanding of the academic profession, institutional missions, and the strategic role of universities in driving knowledge, innovation, and societal progress. GALEP 1.0 was designed as a response to this need. It is a structured learning and development initiative that aims to prepare young and emerging academic leaders with a robust set of leadership competencies essential for scholarship development, institutional advancement and academic excellence.The programme adopts a holistic framework that not only builds theoretical knowledge, but also cultivates practical leadership skills and context-sensitive strategies.